Equipment for linking the AutoAnalyzer on-line to a computer. Issue 2 (March 1971) - Simpson, D.; Sims, G. E.; Harrison, M. I.; Whitby, L. G.
Abstract : An Elliott 903 computer with 8K central core store and magnetic tape backing store has been operated for approximately 20 months in a clinical chemistry laboratory. Details of the equipment designed for linking AutoAnalyzers on-line to the computer are described, and data presented concerning the time required by the computer for different processes. The reliability of the various components in daily operation is discussed. Limitations in the system's capabilities have been defined, and ways of overcoming these are delineated. At present, routine operations include the preparation of worksheets for a limited range of tests (five channels), monitoring of up to 11 AutoAnalyzer channels at a time on a seven-day week basis (with process control and automatic calculation of results), and the provision of quality control data. Cumulative reports can be printed out on those analyses for which computer-prepared worksheets are provided but the system will require extension before these can be issued sufficiently rapidly for routine use.